2003
DOI: 10.1080/713847125
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Placebo-Controlled, Double Blind, Crossover Design Trial of the Efficacy and Safety of Zestra for Women in Women With and Without Female Sexual Arousal Disorder

Abstract: Zestra for Women is a botanical feminine massage oil formulated to enhance female sexual pleasure and arousal when applied to the vulva. We conducted this randomized, double-blinded, crossover study to evaluate the efficacy and safety of Zestra for Women compared to placebo oil in 10 women with and 10 women without female sexual arousal disorder (FSAD) in conditions of home use in conjunction with sexual activities. Subjects were screened by physical examination, sex therapist interviews, and questionnaires. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The study showed that Zestra users experienced improved desire, arousal, and orgasm compared with placebo, as measured by multiple questionnaires. The study showed Zestra was equally effective in women with normal sexual functioning, FSAD, and in users of SSRIs . A follow‐up, double‐blind, placebo‐controlled study of 256 women with acquired mixed desire/interest/arousal/orgasm disorders showed mixed results.…”
Section: Cannabis‐enhanced Productsmentioning
confidence: 97%
“…The study showed that Zestra users experienced improved desire, arousal, and orgasm compared with placebo, as measured by multiple questionnaires. The study showed Zestra was equally effective in women with normal sexual functioning, FSAD, and in users of SSRIs . A follow‐up, double‐blind, placebo‐controlled study of 256 women with acquired mixed desire/interest/arousal/orgasm disorders showed mixed results.…”
Section: Cannabis‐enhanced Productsmentioning
confidence: 97%
“…Patients should be encouraged to explore self-stimulation with or without the use of a vibrator. Weak pelvic floor musculature may be an etiology for orgasmic disorder and may improve with pelvic muscle exercises or biofeedback (52). The Eros Therapy may also be of benefit in this subset of women (49).…”
Section: Orgasmic Disordermentioning
confidence: 99%
“…Zestra (Zestra Laboratories, Inc.; Charleston, SC) is a topical botanical formulation of borage seed oil, evening primrose oil, angelica root extract, coleus forskohlii extract, ascorbyl palmitate, and dl-alpha tocopherol [26]. It is promoted to relieve symptoms associated with female sexual dysfunction.…”
Section: Topical Formulationsmentioning
confidence: 99%